Effects of glycolytic-based interval training on anaerobic capacity in soccer players - Polczyk, M.; Zaton, M. (Human Movement, 2015)
Purpose. The aim of this study was to determine the magnitude of changes in anaerobic endurance in response to a training protocol targeting glycolytic capacity. Methods. The study involved 24 soccer players from two U-18 teams. One team served as an experimental (E) group the other a control (C). Besides standard soccer practice performed by both groups, an interval training protocol was administered to the experimental group twice a week (15 sessions). One training repetition involved running a soccerspecific course. Repetition time was equal to 15 s interspersed with 45 s passive recovery. Total number of repetitions was determined by the ability to maintain target time (power) in subsequent repetitions. A 5% reduction in the distance covered (m) compared with the first repetition ended a set. The number of sets was based on the ability of player to maintain target time per repetition. Rest interval between sets was 15 min. Anaerobic performance was assessed before and after the 8-week protocol by the Wingate test in which arterial blood gases, blood lactate concentration, and respiratory variables on a breath-by-breath basis were measured. Results. Distance covered in group E in the first training session was 470.38 ± 77.82 m and 1182.31 ± 164.44 m in the last session. Post-intervention total work (273.63 ± 18.32 to 284.98 ± 15.76 J/kg) and maximum power (13.28 ± 1.43 to 14.14 ± 1.25 W/kg) significantly increased in the Wingate test. Statistically significant increases in lactate concentration (10.64 ± 1.54 and 12.72 ± 1.59 mmol/l) and lower blood pH (7.21 ± 0.03 and 7.19 ± 0.02) were also observed. No significant changes in any of the above variables were observed in group C. Conclusions. Interval training develops glycolytic capacity but with large inter-individual variability.